2006
DOI: 10.1128/aem.00014-06
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Borrelia burgdorferi Sensu Stricto in Peromyscus leucopus , the Primary Reservoir of Lyme Disease in a Region of Endemicity in Southern Maryland

Abstract: In the north central and northeastern United States, Borrelia burgdorferi sensu stricto, the etiologic agent of Lyme disease (LD), is maintained in an enzootic cycle between the vector, Ixodes scapularis, and the primary reservoir host, Peromyscus leucopus. Genetic diversity of the pathogen based on sequencing of two plasmidlocated genes, those for outer surface protein A (ospA) and outer surface protein C (ospC), has been examined in both tick and human specimens at local, regional, and worldwide population s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 73 publications
5
30
0
2
Order By: Relevance
“…Thus, one explanation is that the richness of B. garinii ospC strains in birds is higher than the richness of B. afzelii ospC strains in rodents. To date, most of the studies investigating ospC strain richness in vertebrate reservoir hosts have focused on mammals (1,13,50,52,55,66,82,83). The two studies that investigated birds (81,85) found a mean ospC strain richness (1.00 to 1.76 strains per tick) that was low compared to that found in the studies with mammals, but this could be an artifact of the relatively inefficient molecular methods that were used in the bird studies (RLB assay and Sanger sequencing).…”
Section: Cross-immunity and Co-occurrence Of Borrelia Ospc Strainsmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, one explanation is that the richness of B. garinii ospC strains in birds is higher than the richness of B. afzelii ospC strains in rodents. To date, most of the studies investigating ospC strain richness in vertebrate reservoir hosts have focused on mammals (1,13,50,52,55,66,82,83). The two studies that investigated birds (81,85) found a mean ospC strain richness (1.00 to 1.76 strains per tick) that was low compared to that found in the studies with mammals, but this could be an artifact of the relatively inefficient molecular methods that were used in the bird studies (RLB assay and Sanger sequencing).…”
Section: Cross-immunity and Co-occurrence Of Borrelia Ospc Strainsmentioning
confidence: 77%
“…Several papers have dealt with the nomenclature of the major ospC groups in B. burgdorferi sensu lato (46,47,49,54,65,66). In the United States, workers have developed a wellestablished system of names for the major ospC groups of B. burgdorferi sensu stricto (45).…”
Section: Methodsmentioning
confidence: 99%
“…This laboratory observation is compatible with what is observed in the environment and in the clinic. Although experimental studies on B. burgdorferi are frequently carried out using a single strain, field studies have shown that mixed infections with different B. burgdorferi genotypes occur in ticks and mammalian reservoir hosts (46)(47)(48)(49). In humans, different strains have been isolated from individual Lyme disease patients (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia isolates from small mammals in the field contain highly heterogeneous (both genetically and phenotypically) populations of borreliae, and as demonstrated in this study, following long-term storage of this B. bissettii isolate immunocompetent animals were capable of clearing spirochaetes after needle challenge. However, passage through SCID mice allowed us to select for host-adapted infectious populations of the spirochaete that were subsequently able to infect immunocompetent animals (Anderson & Norris, 2006;Hofmeister et al, 1999). B. bissettii infection results in similar bacterial burdens as B. burgdorferi ss in skin, heart and bladder tissues, but lower burdens in joint tissues Bacterial burdens were determined by qPCR to compare the ability of B. bissettii and B. burgdorferi ss to disseminate throughout and be retained in the tissues of infected animals.…”
Section: B Bissettii Is Able To Infect Immunocompetent Mice Only Aftmentioning
confidence: 99%